PENGARUH LABA BERSIH DAN UKURAN PERUSAHAAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Dyah Ayu; Dwi Rinda Permata Sari Sijabat (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
Effect of Net Profit and Firm Size on Stock Prices in Manufacturing Companies in the Consumer Goods Industry Sector in 2015-2019 Indonesia Stock Exchange (IDX). This research was conducted to determine the effect of net profit and firm size on stock prices in manufacturing companies in the consumer goods industry for the period 20152019. The data used in this study are secondary data listed on the Indonesia Stock Exchange with a purposive sampling method with a research sample of 15 companies from 52 companies in the consumer goods industry sector with a period of 5 years, between year 2015 - 2019. The method of analysis used in this study is statistical test, descriptive, classical assumption test, hypothesis test. Based on this research, the results of the t test (partial) show that the net profit variable has a positive significant effect on the stock prices. Firm size has a negative significant effect on the stock prices. For the results of the F test (simultaneous) shows that the variable net profit and firm size simultaneously have a significant effect on stock price.